The association between albumin levels, platelet-to-albumin ratio, and the likelihood of peritonitis occurrence in individuals undergoing peritoneal dialysis - Mazen, Mazen; Rifai, Achmad; Gunawan, Atma (PT. DEKA RESEARCH INSTITUTE, 2024)
BACKGROUND: Since albumin and platelet had been reported to govern the risk of infection, their impact in the case of peritoneal dialysis (PD) – related peritonitis should be investigated. OBJECTIVES: To assess the association between albumin levels and platelet – to – albumin ratio and the risk of PD-related peritonitis. METHODS: We conducted a retrospective study in Saiful Anwar General Hospital, Malang, Indonesia during July 2019 and July 2021. Data related to albumin levels and platelet – to – albumin ratio as well as the incidence of PD-related peritonitis were collected from medical record using a standardized pilot form. The association between the albumin levels and platelet – to – albumin ratio and the risk of PD-related peritonitis was analyzed using multiple logistic regression. RESULTS: We included 123 PD patients during study period. Of them, 20 patients were PD-related peritonitis. Our study found that lower albumin levels were associated with increased risk of PD-related peritonitis with the mean difference was -0.30 (MD: -0.30; 95%CI: [-0.55], [-0.05]). We also found that platelet – to – albumin ratio was observed higher in PD-related to peritonitis compared to control (MD: 14420.10; 95%CI: 832.08, 28008.12). However, the role of albumin levels and platelet – to – albumin ratio had weak association to the risk of PD-related peritonitis with the area under curve were 61% and 59%, respectively. CONCLUSION: Our study provides the preliminary data regarding the potential role of albumin and platelet – to – albumin ratio for predicting the risk of PD-related peritonitis. However, further large – scale study should be performed to reclarify our findings.